Korelasi Dimensi Perusahaan, Pendapatan Pergadaian, serta Tingkat Inflasi dengan Peningkatan Penyaluran Kredit pada Perusahaan Pergadaian Swasta di Indonesia - Rais, Sasli; Windarko, Windarko (Eastasouth Institute, 2025)
The number of private pawnbrokers in Indonesia is increasing, but their contribution, particularly to credit distribution, is relatively small. This research aims to identify the correlation between company dimensions, pawnbroker income, and the inflation rate, with increased credit distribution. This study examines the strength of the correlation between the variables of company dimensions, pawnbroker income, and the inflation rate with credit distribution. This research uses a quantitative correlational method. The data collection technique uses purposive sampling. The data collection method is secondary, using annual time series data from 2016 to 2024. The analysis method uses multiple linear regression. The results of this research conclude that, in part, company dimensions and pawnbroker income have a positive effect on credit distribution. The inflation rate has a positive and very strong correlation between company dimensions and pawnbroker income with credit distribution. The inflation rate has a positive but less strong correlation with credit distribution. However, simultaneously, there is a positive influence and a positive correlation between company dimensions, pawnbroker income, and the inflation rate with increased credit distribution in private pawnbrokers.